Similarities and differences between papal discourses and presidential speeches: wishes, values, scenarios, spaces and agents - Maldavsky, David; Plut, SebastiÃ¡n (JOURNAL OF ADVANCES IN LINGUISTICS, 2015)
The paper details in the first place the frequency distributions in the analysis of wishes in words in papal speeches and then compares them with the frequency distributions in the analysis of wishes in words in presidential speeches. The differences detected between both analyses let us infer that words such as truth, love and beauty are more relevant in papal speeches, whereas the ideals of winning, justice and dignity prevail in presidential speeches. Moreover, there are differences between these speeches in terms of the kind of scenario narrated, the spatial concept, the colleagues, etc.